Unique amino acid substitutions in the capsid proteins of foot-and-mouth disease virus from a persistent infection in cell culture. - Díez, J (1990)
Maintenance of a persistent foot-and-mouth disease virus (FMDV) infection in BHK-21 cells involves a coevolution of cells and virus (J. C. de la Torre, E. Martínez-Salas, J. Díez, A. Villaverde, F. Gebauer, E. Rocha, M. Dávila, and E. Domingo, J. Virol. 62:2050-2058, 1988). The resident FMDV undergoes a number of phenotypic changes, including a gradual decrease in virion stability. Here we report the nucleotide sequence of the P1 genomic segment of the virus rescued after 100 passages of the carrier cells (R100). Only 5 of 15 mutations in P1 of R100 were silent. Nine amino acid substitutions were fixed on the viral capsid during persistence, and three of the variant amino acids are not represented in the corresponding position of any picornavirus sequenced to date. Cysteine at position 7 of VP3, that provides disulfide bridges at the FMDV fivefold axis, was substituted by valine, as determined by RNA, cDNA, and protein sequencing. The modified virus shows high buoyant density in cesium chloride and depicts the same sensitivity to photoinactivation by intercalating dyes as the parental FMDV C-S8c1. Amino acid substitutions fixed in VP1 resulted in altered antigenicity, as revealed by reactivity with monoclonal antibodies. In addition to defining at the molecular level the alterations the FMDV capsid underwent during persistence, the results show that positions which are highly invariant in an RNA genome may change when viral replication occurs in a modified environment.